Pengaruh Budaya Organisasi Terhadap Kinerja Organisasi - Faisal Reza; Ira Valentina Silalahi (ArtComm, 2021)
Organizational culture is one of the most important constructs in management research. The purpose of this exploratory study is to determine the impact of organizational culture on organizational performance in order to find out how organizational culture helps in improving organizational performance. This study uses a descriptive approach by examining the results of several existing empirical studies. The findings indicate that all cultural dimensions influence different perspectives of organizational performance. Other studies reveal that organizational culture has an influence on company performance in terms of stability, competitiveness and performance orientation. Organizational culture has a profound impact on organizational processes, employees and their performance. The same research shows that if employees are committed and have the same norms, it can improve performance to achieve overall organizational goals. Leaders are recommended to develop a strong culture in the organization to improve employee and organizational performance. For this reason, this article will examine, based on empirical research, the relationship between culture and organizational performance.